The basic concept for the democracy ranking of the quality of democracy - Campbell, David F. J. (2008)
Abstract: "The following paper presents the basic concept for the Democracy Ranking of the Quality of Democracy and positions this approach in context of academic discourses about democracy and the quality of democracy. Key dimensions of democracy are freedom, equality and control. Quality-of-democracy models commonly emphasize a democracy understanding that is broader than earlier concepts of primarily electoral democracies. Different global democracy and democratization measurement initiatives (Freedom House, Polity IV, Vanhanen’s Index of Democracy, and the Economist Intelligence Unit's Index of Democracy) are reviewed and compared. The Democracy Ranking underscores a conceptualization of the Quality of Democracy = Quality of Politics + Quality of Society. The conceptual formula for the Democracy Ranking (see Figure 5 in Chapter 5), therefore, may be summarized as: quality of democracy = (freedom + other characteristics of the political system) + (performance of the nonpolitical dimension